ANALISIS KEPUTUSAN INVESTASI DAN KEBIJAKAN PENDANAAN TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTI DI INDONESIA - Tri Cicik Wijayanti (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyse the impact of investment decisions and financing policies on company value in the property sector in Indonesia through a literature review approach. As a capital-intensive industry, the property sector requires strategic decision-making in both project investment and capital structure to maintain business growth and competitiveness. Investment decisions are analysed based on their ability to generate long- term returns, increase profitability, and strengthen investor confidence. Meanwhile, financing policies are examined based on their role in optimising the balance between debt and equity, managing financial risk, and maintaining corporate liquidity. By synthesising findings from previous empirical studies and various financial theories such as the Trade- Ofl Theory and Pecking Order Theory, this study demonstrates that the synergy between appropriate investment allocation and efficient financing structure is key to achieving sustainable corporate value. This research contributes theoretically by emphasising the interconnection between investment and financing strategies in value creation, as well as practically by providing insights for property sector management to adapt to market dynamics, macroeconomic conditions, and regulatory policies.